Great enhancement of mechanical features in PLA based composites containing aligned few layer graphene (FLG), the effect of FLG loading, size, and dispersion on mechanical and thermal properties. Issue 44 (24th June 2021) - El Marouazi, Hamza; van der Schueren, Benoit; Favier, Damien; Bolley, Anaëlle; Dagorne, Samuel; Dintzer, Thierry; Janowska, Izabela
Abstract: Four series of polylactide (PLA) based composite films containing horizontally aligned few layer graphene (FLG) flakes of high aspect ratio and adsorbed albumin are prepared. The mechanical and thermal properties varies with percentage, dispersion degree and size of FLG flakes. Great improvement up to 290% and 360% of tensile modulus and strength respectively were obtained for the composite containing high lateral size of FLG at 0.17% wt, and up to 60% and 80% for the composite with very well dispersed 0.02% wt FLG. The composites of PLA and PEG‐PLLA containing very well dispersed FLG flakes at 0.07% wt are ductile showing enhancement of elongation at break up to respectively 80% and 88%. Relatively high electrical conductivity, 5 × 10 −3  S/cm, is measured for PLA film charged with 3% of FLG. Abstract : The introduction of few layer graphene (FLG) (functionalized with serum albumin, obtained via sustainable exfoliation) into polylactide films significantly enhances the mechanical properties of the polymer. The horizontal alignment of FLG with its well crystalline structure and dispersion allows to obtain this enhancement at very low FLG loading, uncomparably lower to the common r(GO) based additive.